Comparison of outcomes following stereotactic body radiotherapy for non-small cell lung cancer in patients with and without pathological confirmation. (February 2014) - Haidar, Yarah M.; Rahn, Douglas A.; Nath, Sameer; Song, William; Bazhenova, Lyudmila; Makani, Samir; Fuster, Mark M.; Sandhu, Ajay P.
Purpose/objective: Treatment of presumed early-stage lung cancer with definitive radiation therapy in the absence of a pathologically confirmed specimen frequently occurs. However, it is not well described in the literature, and there are few North American series reporting on this patient population. We report outcomes in patients treated with stereotactic body radiotherapy (SBRT) for presumed lung cancer and compare them to outcomes in patients treated with SBRT with pathologically confirmed non-small cell lung cancer (NSCLC). Materials/methods: This study is based on a retrospective review of 55 patients with presumed or confirmed lung cancer: 23 patients had nondiagnostic or absent pathologic specimens while 32 patients had pathologically confirmed NSCLC. All patients had hypermetabolic primary lesions on a positron emission tomography (PET) or PET/computed tomography (CT) scan. SBRT was delivered as 48–56 Gy in four to five fractions via a four-dimensional CT treatment plan. Results: Of the patients without pathological confirmation, the mean age was 78 (range 63–89 years) and 17 (74%) were men. The mean tumor size was 2.5 cm (range 1.0–5.1). Reasons for not having confirmed pathologic diagnosis included indeterminate biopsy specimen or an inability to tolerate a biopsy procedure due to poor respiratory status. SBRT was chosen due to noncandidacy for surgery in 17 patients (74%) or patient refusal of surgery in six (26%). Median follow up was 24.2 months (range 1.9–64.6): 2 of the 23 patients (8.7%) had local failure at the site of SBRT and 3 (13%) had regional failure. The actuarial 12-month overall survival was 83%. The median overall survival was 30.2 months. At last follow up, 12 patients (52%) were alive up to 64.6 months after treatment. SBRT was tolerated well in this series. Acute toxicity was noted in two patients (8.7%) and chronic toxicity in three (13%). These patient characteristics and results were shown to be similar to the 32 patients with pathologically confirmed NSCLC. On Kaplan–Meier analysis, there was no significant difference ( p = 0.27) in overall survival between patients with pathologically confirmed NSCLC and those with presumed lung cancer (which was deemed most likely NSCLC). Conclusion: While biopsy confirmation remains a goal in the workup of suspected NSCLC, SBRT without pathologic confirmation may represent a safe and effective option for the treatment of presumed NSCLC among patients who cannot tolerate or refuse surgery.